2011
DOI: 10.4318/tjg.2011.0152
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of children with celiac disease to different hepatitis B vaccination protocols

Abstract: Celiac disease (CD) is a common autoimmune disease characterized by permanent intolerance to ingested gluten, which results in immune-mediated injury of the small bowel mucosa. Genetic, environmental and immunological factors are responsible for the disease. Susceptibility to CD is determined, in part, by a common human leukocyte antigen (HLA) association; specifically, the major histocompatibility complex class II antigen DQ2, which is present in 86% to 100% of the patients (1).Hepatitis B virus (HBV) infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Whether patients with CD have non-protective antibody responses to HBV vaccination more frequently than non-affected subjects is still debated in the literature. [6][7][8][9][10][11][12] This issue has not yet been addressed by systematic reviews or meta-analyses. The results of a meta-analysis dealing with the immune response to HBV vaccination in celiac disease could provide information for clinical practice guidelines for CD patient management, since HBV infection is a relevant topic in all age groups, and a crucial issue for people belonging to high risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…The total study group included 64 CD children (group 1 who received HBV vaccination at birth, 2 and 9-12 months of life, and group 2 at birth, 1 and 6 months of life) and 49 healthy controls. The authors found that the response rate to HBV vaccine and anti-HBs titers in CD patients who completed the HBV vaccination before 1 year of age were signiicantly lower compared to healthy controls, whereas no statistically signiicant diference was observed with the two diferent HBV vaccination schedules [24]. Ertekin et al compared the response to HBV vaccine between children with CD and healthy children and investigated the relationship between the patients' responses to HBV vaccine, the clinical presentation of CD, and the dietary compliance in the patients.…”
Section: Responses To Vaccinations In Celiac Childrenmentioning
confidence: 96%
“…The failure of CD subjects to respond to HBV vaccination has great importance for public health policies as the nonresponders could be regarded as a reservoir for HBV [20]. The studies that have addressed the relation between CD and HBV vaccination in children are summarized in Table 1 [21][22][23][24][25][26][27][28][29]. In the earliest report involving 26 celiac patients aged 9.2 ± 4.6 years and 18 age-matched controls, receiving the full complement of childhood vaccination (HBV, tetanus, rubella, Haemophilus inluenzae type b), Park et al [21] demonstrated that a signiicantly higher proportion of subjects in the CD group failed to respond to HBV vaccine compared with controls (53.9% versus 11.1%; p < 0.05).…”
Section: Responses To Vaccinations In Celiac Childrenmentioning
confidence: 99%
“…It was concluded that GFD and compliance to diet, rather than the specific HLA alleles may increase the immune response to HBV vaccination in CD patients[13]. Balamtekın et al[14] compared the rates of seroconversion to HBV vaccine in the first year of life, utilizing two different immunization schedules. The entire study population consisted of 64 CD children (group 1 who received HBV vaccination at birth, at 2 mo and at 9-12 mo of life and group 2, at birth, 1 mo and 6 mo of life), and 49 healthy controls.…”
Section: Responses To Vaccinations In Children With Celiac Diseasementioning
confidence: 99%